SOSIALISASI PENDAMPINGAN PEMBUATAN SERTIFIKAT HALAL UNTUK UMKM DESA RAWANG PASAR IV - Dewi Astuti; Datulina Ginting; Nova Eliza Silaen; Muhammad Sepristiwanto; Juwita Andri Syafitri; Fikri Ikhsan Drajat; Annisa Wardana Ningsih; Meilia Anjelina; Ninda Septiana (Smart Education, 2024)
Abstract: The purpose of the service activity is to provide an understanding of the importance of halal certificates for MSME players, assist in the registration and processing of halal certificates, increase consumer confidence in Rawang Pasar IV Village MSME products, and encourage improvements in the quality and competitiveness of local products. Halal certification was chosen as the focus because the increasing demand for halal products provides a great opportunity for MSMEs in Rawang Pasar IV Village to develop a wider market. The promotion of halal certificates is an important step in increasing competitiveness and consumer confidence in MSME products. The methods used in this service include socialization, lectures and questions and answers with the participants as well as assistance in the halal certification application process. Through this service, village MSMEs are equipped with knowledge about halal certification requirements, good production management and effective marketing. Apart from that, assistance is also provided in managing the halal certification process so that MSMEs can meet the set standards. Keyword: halal certificate, msmes, halal standards. Abstrak: Tujuan kegiatan pengabdian adalah untuk memberikan pemahaman tentang pentingnya sertifikat halal bagi pelaku UMKM, mendampingi proses pendaftaran dan pengurusan sertifikat halal, meningkatkan kepercayaan konsumen terhadap produk UMKM Desa Rawang Pasar IV, dan mendorong peningkatan kualitas dan daya saing produk lokal. Sertifikasi halal dipilih sebagai fokus karena permintaan produk halal yang semakin meningkat memberikan peluang besar bagi UMKM Desa Rawang Pasar IV untuk mengembangkan pasar lebih luas. Sosialisasi sertifikat halal merupakan langkah penting dalam meningkatkan daya saing dan kepercayaan konsumen terhadap produk UMKM. Metode yang digunakan dalam pengabdian ini meliputi sosialisasi, ceramah dan tanya jawab dengan para peserta serta pendampingan dalam proses pengajuan sertifikasi halal. Melalui pengabdian ini, UMKM desa dibekali dengan pengetahuan tentang persyaratan sertifikasi halal, tata kelola produksi yang baik, dan pemasaran yang efektif. Selain itu, pendampingan juga diberikan dalam mengurus proses sertifikasi halal agar UMKM dapat memenuhi standar yang ditetapkan.Kata kunci: sertifikat halal, umkm, standar kehalalan.